UNDERSTANDING “VERLAN” IN THE FRENCH LANGUAGE - Radjabov Ruslan Rajabmurodovich (Web of Journals Publishing, 2025)
Verlan (verlan français) is an unusual and creative form of French slang, characterized by the replacement of letters or syllables of sounds and words, word cutting, inversion, and the creation of new terms with changed meanings. This “reverse” spelling, formed by changing the syllables or sounds of a word, allows speakers to communicate with a touch of irony, wit, and originality. Verlan is widely used in French urban culture, especially among young people, immigrants, and subcultures such as hip-hop and rap. In this article, we will examine in detail the history, rules, and methods of use of French verlan with examples.
Keywords: Verlan, letter, syllable, words and sentences, reverse pronunciation, word cutting, inversion, slang, Parisian culture.